PEMBANGUNAN KAPAL PERIKANAN DI GALANGAN KAPAL TRADISIONAL KALIMANTAN SELATAN - Rusmilyansari Rusmilyansari; Iriansyah Iriansyah; Irhamsyah Irhamsyah (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
Fishing vessel is one element in determining the success of fishing operations. This study aims to determine; (1) the level of technology; (2) the type of wood used, and (3) the stageof development of timber ships in the traditional ship yard. The study was conducted by Survey. Research conducted ship yard Sewangi Barito Kuala district and village Pagaruyung Tanah Bumbu Regency South Kalimantan. The study was conducted in August through October 2013. Results showed that: ( 1 ) The level of technology used in the construction of the ship is still relatively low , the equipment used is still using nonelectronic equipment ie axes, saws, chisels, pegs, hammer, machetes, bacci, measuring instruments, planers. Only the use of an electric drill workmanship. The level oftechnology in the construction of timber ships has not been completed by the calculationof shipping architecture and ship design and construction drawings ; ( 2 ) type of wood used is Ulin wood, Alaban, Bengkirai, Bungur and Meranti which have a high degree of strength and resistant to attack by marine organisms; ( 3 ) Stages of development oftraditional boats to large ships began with the manufacture of the hull, keel assembly tothe deck and transom beam. As for the small boat begins with the manufacture of thevessel tree seedlings. The next stage is good for big ships and small ships are mountingLinggi bow and stern, leather installation vessel up to half the height of the ship,Installation joist left and right, galar installation, installation of ship skin entirely to sheer,sheer installation, flooring installation deck, pemakalan, rig manufacturing of largevessels and final are painting